Management Project-Academic Research Document - Bhasin, Anupam (2012)
The Indian education industry has seen increasing growth over recent years. With the demand for quality education there has been an increase in the overall number of schools across India. Industry reports have estimated the primary and secondary education sector to grow at a compounded annual growth rate (CAGR) of 14% approximately. Interest has been shown both by the government as well as the private sector in the education segment. Over 90% of the government spending in the education sector flows into the Kindergarten to 12th (K-12) segment. The k-12 sector is expected to reach USD 50 Billion by 2015 as compared to USD 24.5 Billion in 2008.It is evident that this sector has tremendous potential and growth but at the same time is highly unorganised. While there are several opportunities prevalent in this sector they need not always be identified and catered to by companies. (Oifc, 2012) For any business, it is extremely important to have a right strategy in place, Entrepreneurs today are looking for strategies to identify and exploit opportunities. Every firm has its own resources with this study we aim to analyse ways of effectively utilising them in order to increase the overall opportunities and gain competitive advantage. The report aims to understand the meaning of entrepreneurial opportunities (i.e.) understand their nature and characteristics. By doing so it also aims to study the usage of resources by firms. It further explains the concept of strategic management and entrepreneurship and tries to identify the importance of their integration. It also studies the importance and need of entrepreneurial orientation understanding the functioning of firms of different sizes. The report uses qualitative research in terms of interviewing entrepreneurs/executives engaged within the Indian education sector. With their experience and knowledge, these experts would be able to provide necessary insights relevant to this report. By further analysing various existing entrepreneurial strategies, this report also aims to study strategies adopted by firms and their outcomes. This further leads to identifying how firms actually discover and exploit resources in order to create value and sustain competitive advantage.